Wear-resistant and corrosion-resistant coating for cooker and production process thereof

By adopting chromium-nickel alloy-ceramic-silicon oxide-titanium alloy multi-layer gradient composite coating structure on non-stick cookware, and using modified silica and ion implantation technology, the problem of poor binding force of titanium coating is solved. , significantly improves the wear resistance, corrosion resistance and non-stick properties of the cooker.

CN119307918APending Publication Date: 2025-01-14YONGKANG WENGSHI HOUSEHOLD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411453494.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The titanium coating of existing non-stick cookware has poor bonding power with the cookware body, causing the coating to fall off, affecting the non-stick performance, and insufficient high-temperature resistance and wear resistance.

Method used

Using a multi-layer gradient composite coating structure, the bottom layer is a chromium-nickel alloy layer, the middle layer is a ceramic-silicon oxide composite material layer, and the outer layer is a titanium alloy layer, and the binding force is enhanced by modified silica and ion implantation technology. and wear resistance.

Benefits of technology

It improves the binding force, corrosion resistance and non-stick properties of the coating, enhances overall performance and stability, solves the problem of insufficient binding force of the titanium coating, and improves the wear resistance, corrosion resistance and non-stick properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005089814290000111
    Figure BDA0005089814290000111
  • Figure BDA0005089814290000121
    Figure BDA0005089814290000121
Patent Text Reader

Abstract

The invention provides a wear-resistant and corrosion-resistant coating for a cooker and a production process of the wear-resistant and corrosion-resistant coating. The coating comprises a bottom layer, a middle layer and an outer layer, the bottom layer is a chromium-nickel alloy layer, the middle layer is a ceramic-silicon oxide composite material layer, and the outer layer is a titanium alloy layer; the bottom layer comprises the following raw materials in parts by weight: 30-50 parts of iron powder, 20-30 parts of chromium powder, 10-15 parts of nickel powder, 4-8 parts of manganese powder and 4-8 parts of molybdenum powder; the middle layer is prepared from the following raw materials in parts by weight: 40 to 50 parts of aluminum oxide powder, 35 to 45 parts of zirconium dioxide powder, 5 to 15 parts of hafnium dioxide powder, 10 to 20 parts of modified silicon dioxide powder and 4 to 6 parts of boron nitride; and the outer layer comprises the following raw materials in parts by weight: 95-100 parts of titanium powder, 1-2 parts of vanadium powder, 0.1-0.3 part of iron powder and 0.1-0.3 part of copper powder. The bottom layer enhances the binding force with a base material, the middle layer provides excellent adhesive force and corrosion resistance and plays a role of a buffer layer, and the outer layer provides good non-sticky performance and high temperature resistance. Through the synergistic effect of all the layers, the problem that the binding force between the base material and the titanium coating is insufficient is solved, and meanwhile the performance of the coating is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, and in particular to a wear-resistant and corrosion-resistant coating for cookers and a production process thereof. Background Art

[0002] Non-stick cookware, as the name implies, is a type of cookware that does not easily adhere to the bottom of the cookware during the cooking process. Its unique coating design allows ingredients to slide easily during cooking, greatly reducing the amount of grease used, while also making cleaning easier, bringing great convenience to kitchen life. There are many types of non-stick cookware, mainly including ceramic non-stick cookware, Teflon non-stick cookware, and titanium-coated non-stick cookware. Ceramic non-stick cookware does not release harmful gases to the human body during cooking, ensuring the safety of food. The ceramic material can withstand temperatures of up to 450°C or even 500°C, and can adapt to most cooking needs, including high-temperature stir-frying and deep-frying, without producing harmful substances. However, the thermal expansion coefficient of ceramic materials is small, and rapid heating or cooling may cause the coating to deform and crack, which greatly reduces the non-stick performance. Teflon non-stick cookware has a low friction coefficient, which makes it difficult for food to adhere to the bottom of the cookware during cooking. It is very convenient to cook and clean. The Teflon coating has good resistance to chemicals such as acids and alkalis and is not easy to be corroded. However, the Teflon coating has poor high temperature resistance. When the temperature exceeds 260°C, the coating may begin to decompose and may release harmful gases. Therefore, it is not suitable for high-temperature cooking, such as long-term frying. In addition, the hardness and strength of the Teflon coating are relatively low, and it is easy to be scratched by sharp objects or hard kitchen utensils, which greatly reduces the non-stick performance. Titanium-coated non-stick cookware, as an emerging type, has particularly outstanding advantages. Titanium is a chemically stable metal with excellent wear resistance, corrosion resistance and high temperature resistance. Therefore, titanium-coated non-stick cookware not only inherits the characteristics of traditional non-stick cookware such as easy cleaning and less oil smoke, but is also more wear-resistant, corrosion-resistant and durable. At the same time, the titanium coating also has certain antibacterial properties, which is healthier and safer. However, the titanium coating has poor bonding with the cookware body, which can easily cause the coating to fall off, thereby affecting the non-stick performance of the cookware. Summary of the invention

[0003] In view of this, the present invention proposes a wear-resistant and corrosion-resistant coating for cookers and a production process thereof to solve the above problems.

[0004] The technical solution of the present invention is implemented as follows: A wear-resistant and corrosion-resistant coating for cookware, comprising a bottom layer, an intermediate layer, and an outer layer. The bottom layer is a chromium-nickel alloy layer, the intermediate layer is a ceramic-silicon oxide composite material layer, and the outer layer is a titanium alloy layer. The bottom layer comprises the following raw materials by weight: 30-50 parts of iron powder, 20-30 parts of chromium powder, 10-15 parts of nickel powder, 4-8 parts of manganese powder, and 4-8 parts of molybdenum powder. The intermediate layer comprises the following raw materials by weight: 40-50 parts of aluminum oxide powder, 35-45 parts of zirconium dioxide powder, 5-15 parts of hafnium dioxide powder, 10-20 parts of modified silicon dioxide powder, and 4-6 parts of boron nitride. The outer layer comprises the following raw materials by weight: 95-100 parts of titanium powder, 1-2 parts of vanadium powder, 0.1-0.3 parts of iron powder, and 0.1-0.3 parts of copper powder.

[0005] Further, the bottom layer includes the following raw materials by weight: 40 parts of iron powder, 25 parts of chromium powder, 13 parts of nickel powder, 6 parts of manganese powder, and 6 parts of molybdenum powder. The middle layer includes the following raw materials by weight: 45 parts of aluminum oxide powder, 40 parts of zirconium dioxide powder, 15 parts of modified silicon dioxide powder, 10 parts of hafnium dioxide powder, and 5 parts of boron nitride. The outer layer includes the following raw materials by weight: 98 parts of titanium powder, 1.5 parts of vanadium powder, 0.2 parts of iron powder, and 0.2 parts of copper powder.

[0006] Further, the modified silica powder is prepared by the following method: the silica powder is placed in a 0.1-0.3M hydrochloric acid solution at 75-85°C and soaked for 2-3h, washed with deionized water 2-4 times, and then washed with ethanol 1-2 times to obtain activated silica powder. The activated silica powder is added to a 4-6wt% 3,4-dihydroxyphenylalanine solution, and then a 0.1-0.3wt% sodium bicarbonate solution is added. The mass volume ratio of activated silica powder, 3,4-dihydroxyphenylalanine solution, and sodium bicarbonate solution is 1: (2-4): (0.02-0.10) g / mL, and the reaction is stirred at 300-500r / min for 24-48h. After the reaction is completed, the solid is filtered out and washed with ethanol 2-4 times, and the solid is placed in a dryer and dried at 70-90°C for 10-15h to obtain modified silica powder.

[0007] Furthermore, a production process of a wear-resistant and corrosion-resistant coating for cookware comprises the following steps:

[0008] (1) Degreasing and sandblasting the inner surface of the aluminum or stainless steel cookware body;

[0009] (2) weighing the bottom raw materials by weight, stirring them evenly to obtain slurry I; and depositing a chromium-nickel alloy layer on the inner surface of the non-stick cookware body by magnetron sputtering.

[0010] (3) weighing the intermediate layer raw materials by weight, stirring them evenly to obtain slurry II; using laser to melt slurry II on the surface of the chromium-nickel alloy layer, and depositing a ceramic-silicon oxide composite material layer on the surface of the chromium-nickel alloy layer;

[0011] (4) Weighing the outer layer raw materials by weight, stirring them evenly, and obtaining slurry III; using laser to melt slurry III onto the surface of the ceramic-silicon oxide composite material layer, and depositing a titanium layer on the surface of the ceramic-silicon oxide composite material layer;

[0012] (5) using an ion implantation method to implant nitrogen ions and sulfur ions into the titanium layer to obtain a titanium alloy layer;

[0013] (6) The aluminum-based or stainless steel-based cookware body is placed in a heating device, heated under vacuum conditions, then kept warm, and then naturally cooled with the heating device to obtain a wear-resistant and corrosion-resistant coating for cookware.

[0014] Further, in step (1), the degreasing treatment is as follows: immersing the cooker body in a degreasing agent diluent, soaking for 10-15 minutes, and then taking out the cooker body and washing it with tap water for 2-4 times. The degreasing agent diluent is prepared by diluting the degreasing agent with purified water by 10-20 times, and the degreasing agent is composed of sodium gluconate, sodium silicate, sodium carbonate, C10-14 alkyl EP type polyether, and EP type block copolymer in a mass ratio of (1-2): (4.0-4.5): (4.0-4.5): (0.05-0.15): (0.4-0.6). Sandblasting is as follows: placing the cooker body in a sandblasting device, placing quartz sand of 80-120 mesh in a sandblasting hopper, setting the sandblasting pressure to 0.4-0.6MPa, and the roughness after sandblasting is Ra3.2-6.4.

[0015] Further, the magnetron sputtering process conditions in step (2) are as follows: one of Cr15Ni60, Cr20Ni80, Cr30Ni70, and Cr20Ni30 is used as the target material, the working pressure is 0.4-1.2 Pa, the protective gas is a mixture of argon and nitrogen, the argon flow rate is 30-50 L / min, the nitrogen flow rate is 5-15 L / min, the target power is 400-700 W, the substrate bias is 50-150 V, the magnetic field strength is 200-300 Gauss, the electric field strength is 5-10 V / cm, the sputtering time is 60-80 min, and the sputtering temperature is 250-450° C. The thickness of the chromium-nickel alloy layer is 60-80 μm.

[0016] Furthermore, the laser cladding process parameters in step (3) are: laser power 4000-6000W, scanning speed 10-20mm / S, powder feeding amount 6-20g / min, spot diameter 2-6mm, carried out under inert protection, gas flow rate 10-15L / min, gas pressure 4-6MPa. The inert gas is one of nitrogen, argon and helium. The thickness of the ceramic-silicon oxide composite material layer is 80-140μm.

[0017] Furthermore, the laser cladding process parameters in step (4) are: laser power 1500-3500W, scanning speed 5-10mm / S, powder feeding amount 6-20g / min, spot diameter 2-4mm, carried out under argon protection, argon flow rate 10-15L / min, gas pressure 4-6MPa. The titanium layer thickness is 60-80μm.

[0018] Furthermore, in step (5), ion implantation is performed according to the following scheme: the cooker body is placed in an ion implantation device under the condition of an ambient temperature of 20-25° C. and a humidity of 40-50%, and the vacuum degree is set to 1×10 -4 -1×10 -3 Pa, nitrogen ions were injected, the ion energy was set to 20-30 keV, and the beam density was 1-2 μA / cm 2 The injection time is 30-60min and the injection volume is 1x10 17 -5x10 17 ions / cm 2 Then, sulfur ions were injected, with the ion energy set to 15-25 keV and the beam density set to 0.5-1 μA / cm 2 The injection time is 20-40min and the injection volume is 5x10 16 -1x10 17 ions / cm 2 .

[0019] Furthermore, in step (6), the vacuum condition is 1×10 -4 -1×10 -3 Pa, heat to 800-1000℃, keep warm for 1.5-3.5h, and cool naturally to 20-30℃ along with the heating device.

[0020] Compared with the prior art, the present invention has the following beneficial effects: the present invention realizes a gradual transition and performance matching from the substrate to the coating by setting the coating as a bottom layer of a chromium-nickel alloy layer, a middle layer of a ceramic-silicon oxide composite material, and an outer layer of a titanium alloy layer. The bottom layer enhances the bonding force with the substrate; the middle layer provides excellent adhesion and corrosion resistance, and acts as a buffer layer; the outer layer provides good non-stick performance and high temperature resistance. This multi-layer gradient composite coating solves the problem of insufficient bonding between the substrate and the titanium coating through the synergistic effect between the layers, while improving the performance and stability of the overall coating system.

[0021] The present invention modifies silicon dioxide by 3,4-dihydroxyphenylalanine, introduces catechol groups, enhances the interaction between the middle layer and the bottom layer and the outer layer, helps to form a dense interface layer between the middle layer and the bottom layer and the outer layer, and then enhances the bonding force. At the same time, the catechol group has strong adhesion and can form a stable chemical bond with the bottom coating and the outer coating. Therefore, when silicon dioxide is modified by 3,4-dihydroxyphenylalanine, the modified silicon dioxide can be more effectively combined with the bottom coating and the outer coating, thereby enhancing the bonding force of the entire coating and indirectly improving the wear resistance of the coating.

[0022] The present invention injects nitrogen ions into the titanium layer, and after the nitrogen ions are injected into the titanium layer, a titanium nitride film can be formed on the titanium surface, so that the surface hardness of the titanium alloy is significantly increased. And the titanium nitride film has excellent wear resistance, so after the titanium alloy is treated with nitrogen ion injection, its wear resistance is also significantly improved. By injecting sulfur ions into the titanium layer, after the sulfur ions are injected into the titanium alloy layer, they react with titanium atoms to generate a sulfide phase, forming a sulfide layer with a low friction coefficient, reducing the friction coefficient of the coating surface, and improving the wear resistance of the coating surface. At the same time, the sulfide formed by injecting sulfur ions on the surface of the titanium coating can form a lubricating film, improve the lubrication performance of the coating, further reduce the friction coefficient between the coating and the food, thereby improving the non-stick performance of the titanium alloy layer. And the injection of nitrogen ions and sulfur ions can fill the tiny pores in the titanium layer, thereby reducing the porosity, improving the density of the titanium alloy coating, so that the tightness of the internal structure of the titanium alloy coating is enhanced, which helps to improve the overall performance of the titanium alloy coating. By injecting nitrogen ions and sulfur ions to reduce porosity, the corrosion channel can be effectively blocked, and the erosion of the corrosive medium on the inside of the material can be reduced, thereby improving the corrosion resistance of the material. At the same time, the injection of nitrogen ions and sulfur ions can fill the pores in the titanium layer, making the surface smoother and denser, which helps to reduce the contact area between food and the pot body, thereby improving the non-stick performance of the cookware.

[0023] The zirconium dioxide in the present invention changes from a monoclinic phase to a tetragonal phase at high temperature, and can induce a phase change back to a monoclinic phase under stress, accompanied by volume expansion, thereby absorbing the energy of crack propagation, improving the toughness and thermal shock resistance of the ceramic-silicon oxide composite material, and thus reducing the damage of thermal stress to the coating. In the present invention, hafnium dioxide, aluminum oxide and zirconium dioxide particles interact with each other during laser cladding to form a dense microstructure, which helps to improve the strength and toughness of the coating. At the same time, the addition of hafnium oxide helps to improve the processing performance of the coating, improve the fluidity of the coating, so that the ceramic-silicon oxide composite material layer can better penetrate into the tiny pores on the surface of the chromium-nickel alloy layer, forming a mechanical locking effect, thereby enhancing the bonding force between the coatings. DETAILED DESCRIPTION

[0024] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.

[0025] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.

[0026] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.

[0027] Example 1

[0028] A wear-resistant and corrosion-resistant coating for cookware, comprising a bottom layer, an intermediate layer, and an outer layer. The bottom layer is a chromium-nickel alloy layer, the intermediate layer is a ceramic-silicon oxide composite material layer, and the outer layer is a titanium alloy layer. The bottom layer comprises the following raw materials by weight: 30 parts of iron powder, 20 parts of chromium powder, 10 parts of nickel powder, 4 parts of manganese powder, and 4 parts of molybdenum powder. The intermediate layer comprises the following raw materials by weight: 40 parts of aluminum oxide powder, 35 parts of zirconium dioxide powder, 5 parts of hafnium dioxide powder, 10 parts of modified silicon dioxide powder, and 4 parts of boron nitride. The outer layer comprises the following raw materials by weight: 95 parts of titanium powder, 1-2 parts of vanadium powder, 0.1 parts of iron powder, and 0.1 parts of copper powder. Among them, the modified silicon dioxide powder is prepared by the following method: the silicon dioxide powder is placed in a 0.1M hydrochloric acid solution at 75°C and soaked for 3 hours, washed twice with deionized water, and then washed once with ethanol to obtain activated silicon dioxide powder. Add activated silica powder to 4wt% 3,4-dihydroxyphenylalanine solution, then add 0.1wt% sodium bicarbonate solution, the mass volume ratio of activated silica powder, 3,4-dihydroxyphenylalanine solution, and sodium bicarbonate solution is 1::0.10 g / mL, and stir at 300r / min for 48h. After the reaction is completed, filter out the solids, wash them twice with ethanol, and place the solids in a dryer at 70°C for 15h to obtain modified silica powder.

[0029] Example 2

[0030] A wear-resistant and corrosion-resistant coating for cookware, comprising a bottom layer, an intermediate layer, and an outer layer. The bottom layer is a chromium-nickel alloy layer, the intermediate layer is a ceramic-silicon oxide composite material layer, and the outer layer is a titanium alloy layer. The bottom layer comprises the following raw materials by weight: 50 parts of iron powder, 30 parts of chromium powder, 15 parts of nickel powder, 8 parts of manganese powder, and 8 parts of molybdenum powder. The intermediate layer comprises the following raw materials by weight: 50 parts of aluminum oxide powder, 45 parts of zirconium dioxide powder, 15 parts of hafnium dioxide powder, 20 parts of modified silicon dioxide powder, and 6 parts of boron nitride. The outer layer comprises the following raw materials by weight: 100 parts of titanium powder, 2 parts of vanadium powder, 0.3 parts of iron powder, and 0.3 parts of copper powder. Among them, the modified silicon dioxide powder is prepared by the following method: the silicon dioxide powder is placed in a 0.3M hydrochloric acid solution at 85°C and soaked for 2 hours, washed with deionized water 4 times, and then washed with ethanol 2 times to obtain activated silicon dioxide powder. The activated silica powder was added to a 6wt% 3,4-dihydroxyphenylalanine solution, and then a 0.3wt% sodium bicarbonate solution was added, the mass volume ratio of the activated silica powder, the 3,4-dihydroxyphenylalanine solution, and the sodium bicarbonate solution was 1:2:0.02 g / mL, and the reaction was stirred at 500r / min for 24. After the reaction was completed, the solid was filtered out, washed with ethanol 4 times, and placed in a dryer at 90°C for 10h to obtain modified silica powder.

[0031] Example 3

[0032] A wear-resistant and corrosion-resistant coating for cookware, comprising a bottom layer, an intermediate layer, and an outer layer. The bottom layer is a chromium-nickel alloy layer, the intermediate layer is a ceramic-silicon oxide composite material layer, and the outer layer is a titanium alloy layer. The bottom layer comprises the following raw materials by weight: 40 parts of iron powder, 25 parts of chromium powder, 13 parts of nickel powder, 6 parts of manganese powder, and 6 parts of molybdenum powder. The intermediate layer comprises the following raw materials by weight: 45 parts of aluminum oxide powder, 40 parts of zirconium dioxide powder, 15 parts of modified silicon dioxide powder, 10 parts of hafnium dioxide powder, and 5 parts of boron nitride. The outer layer comprises the following raw materials by weight: 98 parts of titanium powder, 1.5 parts of vanadium powder, 0.2 parts of iron powder, and 0.2 parts of copper powder. Among them, the modified silicon dioxide powder is prepared by the following method: the silicon dioxide powder is placed in a 0.2M hydrochloric acid solution at 80°C and soaked for 2.5 hours, washed with deionized water 3 times, and then washed with ethanol 2 times to obtain activated silicon dioxide powder. Add activated silica powder to 5wt% 3,4-dihydroxyphenylalanine solution, then add 0.2wt% sodium bicarbonate solution, the mass volume ratio of activated silica powder, 3,4-dihydroxyphenylalanine solution, and sodium bicarbonate solution is 1:3:0.06 g / mL, and stir at 400r / min for 36h. After the reaction is completed, filter out the solids, wash them with ethanol 3 times, and place the solids in a dryer at 80°C for 12.5h to obtain modified silica powder.

[0033] The wear-resistant and corrosion-resistant coating for cookers of Examples 1-3 is produced according to the following process, including the following steps:

[0034] (1) Degreasing and sandblasting pretreatment are performed on the inner surface of the aluminum-based or stainless steel-based cookware body; wherein the degreasing treatment is as follows: immersing the cookware body in a degreasing agent diluent for 12.5 minutes, then taking out the cookware body and washing it with tap water for 3 times. The degreasing agent diluent is prepared by diluting the degreasing agent with purified water by 15 times, and the degreasing agent is composed of sodium gluconate, sodium silicate, sodium carbonate, C10-14 alkyl EP type polyether, and EP type block copolymer in a mass ratio of 1.5:4.2:4.2:0.10:0.5. wherein the sandblasting treatment is as follows: placing the cookware body in a sandblasting device, placing quartz sand of 100 mesh in a sandblasting hopper, setting the sandblasting pressure to 0.5 MPa, and the roughness after sandblasting is Ra3.2.

[0035] (2) Weigh the bottom layer raw materials by weight, stir them evenly to obtain slurry I; use magnetron sputtering to deposit a chromium-nickel alloy layer with a thickness of 70 μm on the inner surface of the non-stick cookware body; the magnetron sputtering process conditions are as follows: Cr30Ni70 is used as the target material, the working gas pressure is 0.8 Pa, the protective gas is a mixture of argon and nitrogen, the argon flow rate is 40 L / min, the nitrogen flow rate is 10 L / min, the target power is 550 W, the substrate bias is 100 V, the magnetic field strength is 250 Gauss, the electric field strength is 7.5 V / cm, the sputtering time is 70 min, and the sputtering temperature is 350 °C.

[0036] (3) Weigh the intermediate layer raw materials by weight and stir them evenly to obtain slurry II; use laser to clad the slurry II on the surface of the chromium-nickel alloy layer, and deposit a ceramic-silicon oxide composite material layer with a thickness of 110 μm on the surface of the chromium-nickel alloy layer; the laser cladding process parameters are: laser power 5000 W, scanning speed 15 mm / S, powder feed rate 13 g / min, spot diameter 4 mm, and it is carried out under nitrogen protection, with a gas flow rate of 12.5 L / min and a gas pressure of 5 MPa.

[0037] (4) Weigh the outer layer raw materials by weight and stir them evenly to obtain slurry III; use laser to clad the slurry III on the surface of the ceramic-silicon oxide composite material layer, and deposit a titanium layer with a thickness of 70 μm on the surface of the ceramic-silicon oxide composite material layer; the laser cladding process parameters are: laser power 2500 W, scanning speed 7.5 mm / S, powder feed rate 13 g / min, spot diameter 3 mm, and it is carried out under argon protection, the argon flow rate is 12.5 L / min, and the gas pressure is 5 MPa.

[0038] (5) Using ion implantation, nitrogen ions and sulfur ions are implanted into the titanium layer to obtain a titanium alloy layer. The ion implantation is performed according to the following scheme: the cooker body is placed in an ion injection device under the conditions of an ambient temperature of 22° C. and a humidity of 45%, and the vacuum degree is set to 5×10 -4Pa, nitrogen ions were injected, the ion energy was set to 25 keV, and the beam density was 1.5 μA / cm 2 The injection time is 45 min and the injection volume is 2.5 x 10 17 ions / cm 2 Then sulfur ions were injected, the ion energy was set to 20 keV, and the beam density was 0.75 μA / cm 2 The injection time is 30 min and the injection volume is 7.5x10 16 ions / cm 2 .

[0039] (6) Place the above aluminum-based or stainless steel-based cooker body into a heating device at 5×10 -4 Pa conditions to 900 ° C, and then keep the temperature for 2.5 hours, and then naturally cool to 25 ° C with the heating device to obtain a wear-resistant and corrosion-resistant coating for cookers.

[0040] Example 4

[0041] Compared with Example 3, this embodiment is different in that the production is carried out according to the following process, including the following steps:

[0042] (1) Degreasing and sandblasting pretreatment are performed on the inner surface of the aluminum-based or stainless steel-based cookware body; wherein the degreasing treatment is: immersing the cookware body in a degreasing agent diluent for 10 minutes, then taking out the cookware body and washing it twice with tap water. The degreasing agent diluent is prepared by diluting the degreasing agent with purified water 10 times, and the degreasing agent is composed of sodium gluconate, sodium silicate, sodium carbonate, C10-14 alkyl EP type polyether, and EP type block copolymer in a mass ratio of 1:4.0:4.0:0.05:0.4. wherein the sandblasting treatment is: placing the cookware body in a sandblasting device, placing quartz sand of 80 mesh in a sandblasting hopper, setting the sandblasting pressure to 0.4MPa, and the roughness after sandblasting is Ra6.4.

[0043] (2) Weigh the bottom layer raw materials by weight, stir them evenly to obtain slurry I; use magnetron sputtering to deposit a chromium-nickel alloy layer with a thickness of 60 μm on the inner surface of the non-stick cookware body; the magnetron sputtering process conditions are as follows: Cr15Ni60 is used as the target material, the working gas pressure is 0.4 Pa, the protective gas is a mixture of argon and nitrogen, the argon flow rate is 30 L / min, the nitrogen flow rate is 5 L / min, the target power is 4000 W, the substrate bias is 50 V, the magnetic field strength is 200 Gauss, the electric field strength is 5 V / cm, the sputtering time is 60 min, and the sputtering temperature is 250 °C.

[0044] (3) Weigh the intermediate layer raw materials by weight and stir them evenly to obtain slurry II; use laser to clad the slurry II on the surface of the chromium-nickel alloy layer, and deposit a ceramic-silicon oxide composite material layer with a thickness of 80 μm on the surface of the chromium-nickel alloy layer; the laser cladding process parameters are: laser power 4000 W, scanning speed 10 mm / S, powder feeding amount 6 g / min, spot diameter 2 mm, and it is carried out under argon protection, with a gas flow rate of 10 L / min and a gas pressure of 4 MPa.

[0045] (4) Weigh the outer layer raw materials by weight and stir them evenly to obtain slurry III; use laser to clad the slurry III on the surface of the ceramic-silicon oxide composite material layer, and deposit a titanium layer with a thickness of 60 μm on the surface of the ceramic-silicon oxide composite material layer; the laser cladding process parameters are: laser power 1500 W, scanning speed 5 mm / S, powder feeding amount 6 g / min, spot diameter 2 mm, and it is carried out under argon protection, the argon flow rate is 10 L / min, and the gas pressure is 4 MPa.

[0046] (5) Using ion implantation, nitrogen ions and sulfur ions are implanted into the titanium layer to obtain a titanium alloy layer. The ion implantation is performed according to the following scheme: the cooker body is placed in an ion injection device under the condition of an ambient temperature of 20°C and a humidity of 40%, and the vacuum degree is set to 1×10 -4-3 Pa, nitrogen ions were injected, the ion energy was set to 20 keV, and the beam density was 1 μA / cm 2 The injection time was 30 min and the injection volume was 1x10 17 ions / cm 2 Then sulfur ions were injected, the ion energy was set to 15 keV, and the beam density was 0.5 μA / cm 2 The injection time is 20 min and the injection volume is 5x10 16 ions / cm 2 .

[0047] (6) Place the above-mentioned aluminum-based or stainless steel-based cookware body into a heating device at 1×10 -4 Pa conditions to 800 ° C, and then keep warm for 3.5 hours, and then naturally cool to 20 ° C with the heating device to obtain a wear-resistant and corrosion-resistant coating for cookers.

[0048] Example 5

[0049] Compared with Example 3, this embodiment is different in that the production is carried out according to the following process, including the following steps:

[0050] (1) Degreasing and sandblasting pretreatment are performed on the inner surface of the aluminum-based or stainless steel-based cookware body; wherein the degreasing treatment is: immersing the cookware body in a degreasing agent diluent for 15 minutes, then taking out the cookware body and washing it with tap water for 4 times. The degreasing agent diluent is prepared by diluting the degreasing agent with purified water 20 times, and the degreasing agent is composed of sodium gluconate, sodium silicate, sodium carbonate, C10-14 alkyl EP type polyether, and EP type block copolymer in a mass ratio of 2:4.5:4.5:0.15:0.6. wherein the sandblasting treatment is: placing the cookware body in a sandblasting device, placing quartz sand of size 120 mesh in a sandblasting hopper, setting the sandblasting pressure to 0.6MPa, and the roughness after sandblasting is Ra3.2.

[0051] (2) Weigh the bottom layer raw materials by weight, stir them evenly to obtain slurry I; use magnetron sputtering to deposit a chromium-nickel alloy layer with a thickness of 80 μm on the inner surface of the non-stick cookware body; the magnetron sputtering process conditions are as follows: Cr20Ni30 is used as the target material, the working gas pressure is 1.2 Pa, the protective gas is a mixture of argon and nitrogen, the argon flow rate is 50 L / min, the nitrogen flow rate is 15 L / min, the target power is 700 W, the substrate bias is 150 V, the magnetic field strength is 300 Gauss, the electric field strength is 10 V / cm, the sputtering time is 80 min, and the sputtering temperature is 450 °C.

[0052] (3) Weigh the intermediate layer raw materials by weight and stir them evenly to obtain slurry II; use laser to clad the slurry II on the surface of the chromium-nickel alloy layer, and deposit a ceramic-silicon oxide composite material layer with a thickness of 140 μm on the surface of the chromium-nickel alloy layer; the laser cladding process parameters are: laser power 6000 W, scanning speed 20 mm / S, powder feed rate 20 g / min, spot diameter 6 mm, and it is carried out under helium protection, with a gas flow rate of 15 L / min and a gas pressure of 6 MPa.

[0053] (4) Weigh the outer layer raw materials by weight and stir them evenly to obtain slurry III; use laser to clad the slurry III on the surface of the ceramic-silicon oxide composite material layer, and deposit a titanium layer with a thickness of 60-80 μm on the surface of the ceramic-silicon oxide composite material layer; the laser cladding process parameters are: laser power 3500 W, scanning speed 10 mm / S, powder feed rate 20 g / min, spot diameter 4 mm, and it is carried out under argon protection, the argon flow rate is 15 L / min, and the gas pressure is 6 MPa.

[0054] (5) Using ion implantation, nitrogen ions and sulfur ions are implanted into the titanium layer to obtain a titanium alloy layer. The ion implantation is performed according to the following scheme: the cooker body is placed in an ion injection device under the conditions of an ambient temperature of 25°C and a humidity of 50%, and the vacuum degree is set to 1×10 -4 -1×10 -3Pa, nitrogen ions were injected, the ion energy was set to 30 keV, and the beam density was 2 μA / cm 2 The injection time is 60 min and the injection volume is 5x10 17 ions / cm 2 Then sulfur ions were injected, the ion energy was set to 25 keV, and the beam density was 1 μA / cm 2 The injection time was 40 min and the injection volume was 1x10 17 ions / cm 2 .

[0055] (6) Place the above-mentioned aluminum-based or stainless steel-based cookware body into a heating device at 1×10 -3 Pa conditions to 1000 ° C, then keep warm for 1.5 hours, and then naturally cool to 30 ° C with the heating device to obtain a wear-resistant and corrosion-resistant coating for cookers.

[0056] Comparative Example 1

[0057] Compared with Example 3, the difference between this comparative example is that a wear-resistant and corrosion-resistant coating for cookware is provided, and the coating is a titanium alloy layer, and the titanium alloy layer comprises the following raw materials in parts by weight: 98 parts of titanium powder, 1.5 parts of vanadium powder, 0.2 parts of iron powder, and 0.2 parts of copper powder.

[0058] Comparative Example 2

[0059] The difference between this comparative example and Example 3 is that the silicon dioxide is not subjected to modification treatment.

[0060] Comparative Example 3

[0061] The difference between this comparative example and Example 3 is that in step (5) of the production process of a wear-resistant and corrosion-resistant coating for cookers, only nitrogen ions are implanted into the titanium layer.

[0062] 1. Performance testing

[0063] The non-stick cookware prepared in Examples 1-5 and Comparative Examples 1-3 were tested according to the following test requirements. The test results are shown in Table 1.

[0064] 1.1 Bonding strength test

[0065] Place the cookware sample on the workbench of the scratch tester and tighten it, with the scratch needle perpendicular to the coating of the cookware sample. Start the scratch tester, set the scratch speed to 5mm / min, the loading rate to increase by 10N per minute, and the scratch length to 10cm. Perform the scratch operation according to the above parameters until the coating peels off, and record the load value when the coating peels off. Test each embodiment and each comparative example 5 times and take the average value.

[0066] 1.2 Wear resistance test

[0067] After cleaning the cookware, fix it on the wear tester, set the frequency to 33 times / min, apply a downward force of 15N, use a 70mm long and 30mm wide scouring pad to move back and forth, and the back and forth movement distance is 100mm. Start the tester, replace the scouring pad every 500 times, and observe with a 10x magnifying glass. If the coating surface has a wear mark with a width of more than 1mm on the exposed substrate surface or 10 linear wear marks with a length of more than 2mm on the exposed substrate, stop the test, record the number of cycles at this time, and the total number of cycles before the termination of the test shall prevail.

[0068] 1.3 Acid resistance test

[0069] Pour 2wt% acetic acid into the cooker to about 2 / 3 of its height, cover it and boil it for 10 minutes. Place it at 23℃ for 2 hours, then take it out and rinse it immediately with clean water. Wipe it dry with a soft cloth and check the non-stick surface with a 4x magnifying glass.

[0070] 1.4 Alkali resistance test

[0071] Pour 2wt% sodium carbonate solution into the cooker to about 2 / 3 of its height, place it at 23℃ for 2h, then take it out, rinse it immediately with clean water, wipe it dry with a soft cloth, and check the non-stick surface with a 4x magnifying glass.

[0072] 1.5 Salt water corrosion resistance test

[0073] Inject 5wt% sodium chloride solution into the cooker until the solution reaches more than 1 / 2 of the cooker height, cover the lid, heat to boiling, and keep it slightly boiling, continue heating for 7 hours, and replenish the sodium chloride solution lost due to evaporation during the boiling process with distilled water in time to keep the solution height unchanged. Stop heating, place the cooker at 23℃ for 16 hours, then take it out, immediately rinse the salt stains with clean water, dry the surface with a soft cloth, and immediately conduct a visual inspection.

[0074] 1.6 Non-stick test

[0075] For the non-stickiness test of baked bread, prepare the bread ingredients according to the following proportions: 400g milk, 200g low-gluten flour, 160g egg shells, 4g salt, stir evenly, and leave for 30 minutes. Pour the bread ingredients into the cooker, fill the cooker to about 50% of the capacity, and put it in an electric oven at a temperature of 180℃. Bake until the edge of the bread turns light brown, turn the cooker upside down, pour out the bread, check the bread residue in the cooker, if there is any residue, wipe it gently with a rag. Repeat the above operation for a total of 10 times.

[0076] Table 1

[0077]

[0078]

[0079] It can be seen from Table 1 that Examples 1-5 have excellent performance in terms of bonding strength, wear resistance, corrosion resistance, and non-stickiness, among which Example 3 has the best performance.

[0080] Compared with Example 1, chromium and nickel have good bonding with aluminum or stainless steel. Chromium can form a dense chromium oxide film on the surface of the substrate to enhance the chemical bonding with the substrate; while nickel is tightly bonded to the substrate through physical metallurgy. This bonding provides a solid foundation for the entire coating system. As the bottom layer, the chromium-nickel alloy layer can play a transitional role in terms of thermal expansion coefficient, mechanical properties, etc., reduce the internal stress caused by the performance difference between the substrate and the titanium coating, thereby improving the stability of the overall coating. Ceramics and silicon oxides have excellent adhesion and corrosion resistance, can firmly adhere to the bottom chromium-nickel alloy layer, and provide a good adhesion foundation for the outer titanium coating. At the same time, the intermediate layer can also alleviate the stress concentration caused by factors such as temperature changes and mechanical shocks. When the coating system is subjected to external stress, the intermediate layer can absorb and disperse part of the stress, reduce the impact on the outer titanium alloy layer, thereby maintaining the integrity and corrosion resistance of the coating. Example 3 achieves a gradual transition and performance matching from the substrate to the coating by setting the coating as a bottom layer of a chromium-nickel alloy layer, a middle layer of a ceramic-silicon oxide composite material, and an outer layer of a titanium alloy layer. The bottom layer enhances the bonding force with the substrate; the middle layer provides excellent adhesion and corrosion resistance, and acts as a buffer; the outer layer provides good non-stick performance and high temperature resistance. Through the synergistic effect between the layers, the problem of insufficient bonding between the substrate and the titanium coating is solved, while the performance and stability of the overall coating system are improved, thereby also improving the wear resistance, corrosion resistance, and non-stick performance of the coating.

[0081] Compared with Example 2, in Example 3, silica is modified by 3,4-dihydroxyphenylalanine to introduce catechol groups. The catechol groups have strong coordination ability and can react with metal ions to form a complex, thereby enhancing the interaction between the middle layer and the bottom layer and the outer layer, and helping to form a dense interface layer between the middle layer and the bottom layer and the outer layer, thereby enhancing the binding force. At the same time, the catechol groups have strong adhesion and can form stable chemical bonds with the bottom coating and the outer coating. Therefore, when silica is modified with 3,4-dihydroxyphenylalanine, the modified silica can be more effectively combined with the bottom coating and the outer coating, thereby enhancing the binding force of the entire coating and indirectly improving the wear resistance of the coating.

[0082] Compared with Example 3, after sulfur ions are injected into the titanium alloy layer, they react with titanium atoms to form a sulfide phase, forming a sulfide layer with a low friction coefficient, reducing the friction coefficient of the coating surface and improving the wear resistance of the coating surface. At the same time, the sulfide formed on the surface of the titanium coating by injecting sulfur ions can form a lubricating film, improve the lubrication performance of the coating, further reduce the friction coefficient between the coating and the food, and thus improve the non-stick performance of the titanium alloy layer.

[0083] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A wear-resistant and corrosion-resistant coating for cookware, characterized in that: It comprises a bottom layer, a middle layer and an outer layer; the bottom layer is a chromium-nickel alloy layer, the middle layer is a ceramic-silicon oxide composite material layer, and the outer layer is a titanium alloy layer; the bottom layer comprises the following raw materials in parts by weight: 30-50 parts of iron powder, 20-30 parts of chromium powder, 10-15 parts of nickel powder, 4-8 parts of manganese powder, and 4-8 parts of molybdenum powder; the middle layer comprises the following raw materials in parts by weight: 40-50 parts of aluminum oxide powder, 35-45 parts of zirconium dioxide powder, 5-15 parts of hafnium dioxide powder, 10-20 parts of modified silicon dioxide powder, and 4-6 parts of boron nitride; the outer layer comprises the following raw materials in parts by weight: 95-100 parts of titanium powder, 1-2 parts of vanadium powder, 0.1-0.3 parts of iron powder, and 0.1-0.3 parts of copper powder.

2. The wear-resistant and corrosion-resistant coating for cookware according to claim 1, characterized in that: The bottom layer includes the following raw materials in parts by weight: 40 parts of iron powder, 25 parts of chromium powder, 13 parts of nickel powder, 6 parts of manganese powder, and 6 parts of molybdenum powder; the middle layer includes the following raw materials in parts by weight: 45 parts of aluminum oxide powder, 40 parts of zirconium dioxide powder, 15 parts of modified silicon dioxide powder, 10 parts of hafnium dioxide powder, and 5 parts of boron nitride; the outer layer includes the following raw materials in parts by weight: 98 parts of titanium powder, 1.5 parts of vanadium powder, 0.2 parts of iron powder, and 0.2 parts of copper powder.

3. The wear-resistant and corrosion-resistant coating for cookware according to claim 1, characterized in that: The modified silica powder is prepared by the following method: placing the silica powder in a 0.1-0.3M hydrochloric acid solution at 75-85°C and soaking it for 2-3h, washing it with deionized water for 2-4 times, and then washing it with ethanol for 1-2 times to obtain activated silica powder; adding the activated silica powder to a 4-6wt% 3,4-dihydroxyphenylalanine solution, and then adding a 0.1-0.3wt% sodium bicarbonate solution, wherein the mass volume ratio of the activated silica powder, the 3,4-dihydroxyphenylalanine solution, and the sodium bicarbonate solution is 1:(2-4):(0.02-0.10) g / mL, stirring and reacting at 300-500r / min for 24-48h; after the reaction is completed, filtering out the solid, washing it with ethanol for 2-4 times, placing the solid in a dryer and drying it at 70-90°C for 10-15h to obtain the modified silica powder.

4. The production process of a wear-resistant and corrosion-resistant coating for cookers according to claim 1, characterized in that: The following steps are involved: (1) Degreasing and sandblasting the inner surface of the aluminum or stainless steel cookware body; (2) weighing the bottom raw materials by weight, stirring them evenly to obtain slurry I; and depositing a chromium-nickel alloy layer on the inner surface of the non-stick cookware body by magnetron sputtering. (3) weighing the intermediate layer raw materials by weight, stirring them evenly to obtain slurry II; using laser to melt slurry II on the surface of the chromium-nickel alloy layer, and depositing a ceramic-silicon oxide composite material layer on the surface of the chromium-nickel alloy layer; (4) Weighing the outer layer raw materials by weight, stirring them evenly, and obtaining slurry III; using laser to melt slurry III onto the surface of the ceramic-silicon oxide composite material layer, and depositing a titanium layer on the surface of the ceramic-silicon oxide composite material layer; (5) using an ion implantation method to implant nitrogen ions and sulfur ions into the titanium layer to obtain a titanium alloy layer; (6) The aluminum-based or stainless steel-based cookware body is placed in a heating device, heated under vacuum conditions, then kept warm, and then naturally cooled with the heating device to obtain a wear-resistant and corrosion-resistant coating for cookware.

5. The wear-resistant and corrosion-resistant coating for cookware according to claim 4, characterized in that: The degreasing treatment in step (1) is as follows: immersing the cooker body in a degreasing agent diluent for 10-15 minutes, then taking out the cooker body and washing it with tap water for 2-4 times; the degreasing agent diluent is prepared by diluting the degreasing agent with purified water by 10-20 times, and the degreasing agent is composed of sodium gluconate, sodium silicate, sodium carbonate, C10-14 alkyl EP type polyether, and EP type block copolymer in a mass ratio of (1-2):(4.0-4.5):(4.0-4.5):(0.05-0.15):(0.4-0.6); the sandblasting treatment is as follows: placing the cooker body in a sandblasting device, placing quartz sand with a size of 80-120 mesh in a sandblasting hopper, setting the sandblasting pressure to 0.4-0.6 MPa, and the roughness after sandblasting is Ra3.2-6.

4.

6. The wear-resistant and corrosion-resistant coating for cookware according to claim 4, characterized in that: The magnetron sputtering process conditions in the step (2) are as follows: one of Cr15Ni60, Cr20Ni80, Cr30Ni70, and Cr20Ni30 is used as the target material, the working gas pressure is 0.4-1.2 Pa, the protective gas is a mixture of argon and nitrogen, the argon flow rate is 30-50 L / min, the nitrogen flow rate is 5-15 L / min, the target power is 400-700 W, the substrate bias is 50-150 V, the magnetic field strength is 200-300 Gauss, the electric field strength is 5-10 V / cm, the sputtering is 60-80 min, and the sputtering temperature is 250-450 ° C; the thickness of the chromium-nickel alloy layer is 60-80 μm.

7. The wear-resistant and corrosion-resistant coating for cookware according to claim 4, characterized in that: The laser cladding process parameters in the step (3) are: laser power 4000-6000W, scanning speed 10-20mm / S, powder feeding amount 6-20g / min, spot diameter 2-6mm, carried out under inert protection, gas flow rate 10-15L / min, gas pressure 4-6MPa; the inert gas is one of nitrogen, argon and helium; the thickness of the ceramic-silicon oxide composite material layer is 80-140μm.

8. The production process of a wear-resistant and corrosion-resistant coating for cookers as claimed in claim 4, characterized in that: The laser cladding process parameters in the step (4) are: laser power 1500-3500W, scanning speed 5-10mm / S, powder feeding amount 6-20g / min, spot diameter 2-4mm, carried out under argon protection, argon flow rate 10-15L / min, gas pressure 4-6MPa; the thickness of the titanium layer is 60-80μm.

9. The production process of a wear-resistant and corrosion-resistant coating for cookers as claimed in claim 4, characterized in that: In step (5), ion implantation is performed according to the following scheme: the cooker body is placed in an ion implantation device under the condition of an ambient temperature of 20-25°C and a humidity of 40-50%, and the vacuum degree is set to 1×10 -4 -1×10 -3 Pa, nitrogen ions were injected, the ion energy was set to 20-30 keV, and the beam density was 1-2 μA / cm 2 The injection time is 30-60min and the injection volume is 1x10 17 -5x10 17 ions / cm 2 Then, sulfur ions were injected, with the ion energy set to 15-25 keV and the beam current density set to 0.5-1 μA / cm 2 The injection time is 20-40min and the injection volume is 5x10 16 -1x10 17 ions / cm 2 .

10. The production process of the wear-resistant and corrosion-resistant coating for cookers according to claim 1, characterized in that: The vacuum condition in step (6) is 1×10 -4 -1×10 -3 Pa, heat to 800-1000℃, keep warm for 1.5-3.5h, and cool naturally to 20-30℃ along with the heating device.